The Effect of the Learning Program according to Marzano’s Dimensions Of Learning Model on the Development of the metacognition Thinking Talented Student in Lattakia - Baddour, Lina (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The effect of teaching by using the Learning Program according to Marzano’s Dimensions Of Learning Model in growing the metacognition thinking for first secondary students school in Lattakia. The sample of the research was chosen intentionally , it composedof (58) male and female students, and it follows the curriculum in terms of quasi-experimental sample divided into two groups: (experimental 29 students), and the control group 29 students).And the study used the Learning Program according to Marzano’s Dimensions Of Learning Model for students in first grade secondary school, and Test for metacognition thinking .The study showed that:there was a statistically significant mean score difference between experimental and control groups according to Test for metacognition thinking as a result of the post, so this difference is due to the the metacognition according to Marzano’s Dimensions Of Learning Model, which due to the teaching in this method has contributed to increase the level of students’ metacognition thinking better than the traditional way. And the study didn’t show a statistically significant mean score difference between the mean scores of students of the experimental group (male and female) in the post to test metacognition thinking, and it may be due to the fact that student who learn in a metacognition was an active partner in educational situation, he or she is the tempter, liquid and good listener, all that helped in the development of his metacognition thinking skills, whether male or female.